2023
DOI: 10.23736/s1973-9087.23.07773-0
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of exercise-based cardiac telerehabilitation intervention: a systematic review

Abstract: INTRODUCTION Alternatives such as remotely delivered therapy in the home environment or telehealth represent an opportunity to increase overall cardiac rehabilitation (CR) utilization. Implementing alternatives into regular practice is the next step in development; however, the cost aspect is essential for policymakers. Limited economic budgets lead to cost-effectiveness analyses before implementation. They are appropriate in cases where there is evidence that the compared intervention provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 74 publications
(222 reference statements)
2
23
0
Order By: Relevance
“…Narratively synthesised results favoured home-based care delivered through a telerehabilitation approach, except one used a user manual. This study further confirms the finding by Batalik and colleagues, affirming the cost-effectiveness of exercise-based cardiac telerehabilitation intervention 4. Using a systematic comparison, the costs of providing intervention, unplanned healthcare services usage and incremental cost-effectiveness ratio all favoured home-based CR 4.…”
Section: Commentarysupporting
confidence: 89%
“…Narratively synthesised results favoured home-based care delivered through a telerehabilitation approach, except one used a user manual. This study further confirms the finding by Batalik and colleagues, affirming the cost-effectiveness of exercise-based cardiac telerehabilitation intervention 4. Using a systematic comparison, the costs of providing intervention, unplanned healthcare services usage and incremental cost-effectiveness ratio all favoured home-based CR 4.…”
Section: Commentarysupporting
confidence: 89%
“…The 6MWT is a suitable tool for assessing functional capacity in diabetic patients due to its good acceptability and its easy incorporation into daily living activities; thus appearing as the best among the current walking tests [ 8 ]. A large number of studies have reported the necessity and utility of telehealth through various applications for patients with DM2, including telelearning, telemonitoring, DM self-management, and telecounseling [ 21 , 24 , 41 , 42 ]. Telemedicine studies, such as the research by Milani [ 23 ], have shown that telehealth applications can increase glycemic control, reduce glycated hemoglobin values, and improve the quality of life [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, telehealth could represent a valuable method to improve blood sugar control, prevent rehospitalization, enhance the quality of life, and improve adherence rates to therapeutic interventions in patients with DM2 [ 21 , 22 , 23 ]. Telehealth services also reduce costs and increase the potential to attend more sessions compared to center-based facilities [ 24 ]. Specifically, the COVID-19 pandemic dramatically increased the application of telehealth and the need for reliable remote monitoring of chronic patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are becoming essential tools in Biomedicine and Bioengineering because of their ability to provide accurate, interactive, and immersive simulations of biological systems [ 88 ]. Thus, these technologies make it possible to deliver home-based assessments and interventions or telehealth, potentially offering cost-effective alternatives in several areas [ 59 , 89 ]. Furthermore, multiple practical applications are also emerging in sports sciences to increase the population’s PA levels through exergames, performance enhancement programs with technical or tactical training applications, and sports injuries recovery.…”
Section: Discussionmentioning
confidence: 99%